WANPRESTASI DALAM PELAYANAN PASIEN PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI RUMAH SAKIT ANUTALOKA PARIGI - Azizah, Nur (JURNAL ILMU HUKUM TOPOSANTARO, 2024)
The purpose of this writing is to find out and explain the rights and obligations of BPJS participating patients at Anuntaloka Parigi Hospital, both outpatient and inpatient, to find out what forms of default occur in health services to BPJS participating patients at Anuntaloka Parigi Hospital and to find out and assess the consequences. law if there is a default on a BPJS participant at Anuntaloka Parigi Hospital. This paper uses empirical juridical research. The research results show that BPJS Health Participants have the right to quality services according to the BPJS program with the obligation to comply with the rules. Even though RSD Anuntaloka Parigi fulfills most of the BPJS referral obligations, there are obstacles such as a lack of inpatient space and medical indiscipline. BPJS restrictions on hospital patients can disrupt financing and payment processes, including medical services and patient costs. The lack of clarity regarding the denial of payment, if a patient is readmitted within one month, hurts patients who need ongoing care. The lack of room facilities in hospitals affects the rights of BPJS patients and can cause delays in medical treatment. The legal consequences of default can include claims for compensation for costs, losses, and interest following Article 1239 of the Civil Code, with dispute resolution through various means such as separate execution, arbitration, or through litigation in court. Abstrak Tujuan penulisn ini untuk mengetahui dan menjelaskan hak dan kewajiban pasien peserta BPJS di rumah sakit anuntaloka parigi baik rawat jalan dan rawat inap, untuk mengetahui bagaimana bentuk wanprestasi yang terjadi dalam pelayanan kesehatan kepada pasien peserta BPJS di Rumah Sakit Anuntaloka Parigi dan untuk mengetahui dan mengkaji akibat hukum apabila wanprestasi pada peserta BPJS di rumah sakit Anuntaloka Parigi. Tulisan ini menggunakan penelitian yuridis empiris. Hasil penelitian bahwa Peserta BPJS Kesehatan memiliki hak atas pelayanan berkualitas sesuai program BPJS dengan kewajiban mematuhi aturan. Meskipun RSD Anuntaloka Parigi memenuhi sebagian besar kewajiban rujukan BPJS, terdapat kendala seperti kurangnya ruang inap dan ketidakdisiplinan medis. Pembatasan BPJS pada pasien di rumah sakit dapat mengganggu pembiayaan dan proses pembayaran, termasuk jasa medis dan biaya pasien. Ketidakjelasan terkait penolakan pembayaran jika pasien dirawat kembali dalam satu bulan berdampak buruk pada pasien yang membutuhkan perawatan berkelanjutan. Kurangnya fasilitas kamar di rumah sakit memengaruhi hak pasien BPJS dan dapat menyebabkan keterlambatan tindakan medis. Akibat hukum wanprestasi dapat mencakup tuntutan penggantian biaya, kerugian, dan bunga sesuai Pasal 1239 KUH Perdata, dengan penyelesaian sengketa melalui berbagai cara seperti parate executie, arbitrase, atau melalui proses litigasi di pengadilan.